School libraries' impact on secondary education: a users' study. Issue 6 (26th August 2014) - Bikos, Georgios; Papadimitriou, Panagiota; A. Giannakopoulos, Georgios
Abstract : Purpose: – The purpose of this paper is to offer an overview of students' and teachers' perceptions of school libraries' impact on academic performance in secondary education in Greece, using sociological analysis to assess the data and contextualise it in the particular case and social context of Greece after the crisis. Design/methodology/approach: – This paper developed structured questionnaires for the key categories of users visiting school libraries, teachers and students, trying to explore a set of questions which would give us a better image of their behaviour. The results from our empirical study, following the creation and distribution of a purpose made questionnaire in secondary schools in the area of Athens, was then evaluated in the context of sociological analysis. This paper argued that social factors may explain discrepancy in opinions regarding school libraries' (SLs) role. Findings: – The data which the paper present elucidates, not only the frequency and ways in which pupils of an age up to 14 years use SLs but also their own and their teachers' assumptions as to the degree in which SLs affect their performance. In this way, the data documents currently dominant perceptions of key categories of users in the Greek context but also reveals, via its critical assessment, the kinds of social factors that enhanced or hindered its impact on learning and academic performance in secondary education in Greece. Research limitations/implications: – The paper consists of a study based on a limited sample of users from Greek schools in Athens; hence, its results are indicative. Practical implications: – The paper considers possibilities in which educational and cultural policies in relation to SLs should shift attention following the findings and their interpretation. Social implications: – The paper provides policy implications regarding Greek education. The paper provides some recommendations as to ways in which SLs and research in their users may provide a fresh way of implementing strategies as to their role in Greek education in the period of recession. Originality/value: – This study focuses exclusively on the Greek context, taking into consideration, for the analysis of the data derived from the empirical survey undertaken in Greek schools, sociological parameters tied to the Greek context after the crisis.